Gamification as a tool for enhancing graduate medical education. Issue 1070 (28th October 2014) - Nevin, Christa R; Westfall, Andrew O; Rodriguez, J Martin; Dempsey, Donald M; Cherrington, Andrea; Roy, Brita; Patel, Mukesh; Willig, James H
Abstract: Introduction: The last decade has seen many changes in graduate medical education training in the USA, most notably the implementation of duty hour standards for residents by the Accreditation Council of Graduate Medical Education. As educators are left to balance more limited time available between patient care and resident education, new methods to augment traditional graduate medical education are needed. Objectives: To assess acceptance and use of a novel gamification-based medical knowledge software among internal medicine residents and to determine retention of information presented to participants by this medical knowledge software. Methods: We designed and developed software using principles of gamification to deliver a web-based medical knowledge competition among internal medicine residents at the University of Alabama (UA) at Birmingham and UA at Huntsville in 2012–2013. Residents participated individually and in teams. Participants accessed daily questions and tracked their online leaderboard competition scores through any internet-enabled device. We completed focus groups to assess participant acceptance and analysed software use, retention of knowledge and factors associated with loss of participants (attrition). Results: Acceptance: In focus groups, residents (n=17) reported leaderboards were the most important motivator of participation. Use: 16 427 questions were completed: 28.8% on Saturdays/Sundays, 53.1% between 17:00 and 08:00. Retention of knowledge: 1046 paired responses (for repeated questions) were collected. Correct responses increased by 11.9% (p<0.0001) on retest. Differences per time since question introduction, trainee level and style of play were observed. Attrition: In ordinal regression analyses, completing more questions (0.80 per 10% increase; 0.70 to 0.93) decreased, while postgraduate year 3 class (4.25; 1.44 to 12.55) and non-daily play (4.51; 1.50 to 13.58) increased odds of attrition. Conclusions: Our software-enabled, gamification-based educational intervention was well accepted among our millennial learners. Coupling software with gamification and analysis of trainee use and engagement data can be used to develop strategies to augment learning in time-constrained educational settings.